Swimming Against the Tide: Strategies for Improving Equity in Health - Nancy Birdsall; Robert Hecht (Inter-American Development Bank, Office of the Chief Economist, 1995)
The evidence shows that government spending for health in many developing countries benefits the well-to-do more than the poor. However, a combination of favorable political forces and sound public policies can shift the focus of government expenditures toward the poor. Doing this is an essential part of any effective poverty reduction program in developing countries.
Keywords: 330